Cloacal mycobiota in wild females of Caiman latirostris (Crocodylia: Alligatoridae) - Betiana Núñez-Otaño, Noelia; Ignacio Piña, Carlos; Gonçalves Portelinha, Thiago Costa; Margarita Arambarri, Angélica (Revista mexicana de biodiversidad, 2013)
There are few reports of cloacal mycobiota on wild reptiles, and in particular, fungal presence and function in Caiman latirostris remains unknown. Our objective was to describe the fungal community present in the cloaca of wild female broad-snouted caimans during their reproductive season determine whether the number of fungi has some relationship with the female's corporeal condition. Fungi were found in 9 out of 13 cloacal samples and 14 species of fungi were isolated and identified. Three of the species isolated had the highest occurrence values, and 2 of them are pathogenic. In this case, body condition index had no relationship with fungal frequency; the fungi found in this study may have originated from soil habitat and nest substrate that are in constant contact with the cloaca of the C. latirostris females. The findings in this work support the theory that reptiles are facultative carriers of fungi or their spores. Existen pocos registros acerca de la micobiota cloacal en reptiles silvestres y en particular, la presencia de hongos y su función en Caiman latirostris es aún desconocida. El objetivo de este trabajo fue describir la comunidad fúngica presente en la cloaca de hembras silvestres de Yacaré Overo durante su época reproductiva y analizar si la cantidad de hongos tiene alguna relación con la condición corporal de la hembra. Las hembras que resultaron positivas para hongos fueron 9 de las 13 muestreadas y fueron 14 las especies de hongos aisladas e identificadas. Del total de especies listadas, 3 tienen los valores de abundancia más altos y 2 de ellas son reconocidas como hongos patógenos. La condición corporal no tuvo relación con la frecuencia de hongos en general. Los hongos identificados pudieron tener su origen en el contacto permanente de la cloaca de la hembra de C. latirostris con el suelo del hábitat y/o el sustrato del nido. Los resultados de este trabajo apoyan la teoría de que los reptiles son transportadores facultativos de hongos y/o sus esporas.